Exploring Mindfulness Techniques in Physical Therapy to Address Motor Skill Acquisition: A Perspective Piece - Genevieve Pinto Zipp; Stephanie Bryan (Journal of Basic & Applied Sciences, 2016)
This perspectives piece provides a theoretical frame supporting the exploration of mindfulness techniques as a complimentary interventions strategies for physical therapy interventions to promote motor skill learning especially under dual tasking conditions.